Study guides

Q: What is the difference between the expression x 3 and 3 x?

Write your answer...

Submit

Related questions

3 - x = -(x - 3) x - 3 = -(x - 3)

The expression x - 3 is simply (3 - x) multipled by -1

it has to have an x number in it.

Four times X plus 3 equals seven. 4X + 3 = 7 That!

the difference between a number and 3 is

It factors into (x-3)(x+3) as it follows the difference of squares rule. However, since you gave me an expression and not an equation, I cannot solve this expression beyond this point. If x^2-9=0. Then you can see that (x-3)=0 and (x+3)=0. Thus x=-3, 3.

This is a difference of two square, so you can apply the factoring rule for the difference of two squares.

Equation: x+3=3+x (notice the equal sign: equal; equation)Expression: x+3 (notice no equal sign)

Equation: x+3=3+x (notice the equal sign: equal; equation)Expression: x+3 (notice no equal sign)

(3*x)+4

X = 15 - 5y

- - x + 3 = x + 3

The expression "twice the difference of x and 5" would look like this: 2(x-5). To solve the problem, you would first subtract 5 from x, and then multiply the difference by two.

Simply put, an expression does not need an equal sign, while an equation does. Equation: x+y=z Expression: x+y

x/3

I believe it would be 3-5x (x being the number multiplied by 5)

If your expression is 5x + 4 = ? and x = 3, then the answer is 19. If the expression is 5(x + 4) = ? and x = 3, then the answer is 35.

An expression does not include an equals sign (=) For eg: 2x+3 would not be an equation but an expression However, 2x+3=0, is definitely an equation with a solution x= -3/2. An expression does not have a definite solution. An expression is a set of terms with mathematical operations combining them. An equation consists of two expressions with an equals sign between them. An expression is a collection of terms and does not have an = sign An equation is a collection of terms but has an = sign between them.

The second would suggest that x equals the string "=3".

Radical (3x) = radical(x) * radical(3).

5(x-3)

-(x+3) is one possible answer.

x + 3

It depends what "x" is. ======== An algebraic expression representing the difference (subtraction) between 6 and some unknown number (represented by x).

2 x 2 x 2 x 3 x B x C is the expression.